Influência da seca e inundação nas comunidades microbianas metanogênicas e metanotróficas em planícies aluviais de rios de águas negra, barrenta e clara da Amazônia brasileira - Bento, Marilia de Souza (Universidade Federal de São Carlos, 2019)
Soils from wetland areas contribute significantly to the global methane (CH4) budget. In this sense, this work was designed to evaluate the influence of dry and flooding in the active microbial communities involved in the production and consumption of CH4 in wetland areas under forest and traditional farming system in Amazonian black, white and clear floodplains. Molecular RNA- and 16S ribosomal RNA gene-based analyzes, and soil physicochemical analyzes were performed to reveal the soil methanogenic and methanotrophic microbial communities and investigate the relationships between these microbial communities and the physcochemical factors of soil from forest sites and traditional agricultural systems in two different soil layers (0-15 cm and 15-30 cm) and in two seasonal periods (dry and wet season). Microorganisms belonging to the order Methanocellales dominated the active methanogenic communities in soils of the black floodplain, while these communities were dominated by Methanomasiliicoccales in white and clear floodplains. The methanotrophic communities active in floodplain soils with the different water types were dominated by microorganisms belonging to the NC10 class. This class of bacteria assembles organisms that perform the assimilation of nitrate and nitrite for anaerobic oxidation of CH4. The observed variation in the composition of the active microbial methanogenic and methanotrophic communities among the different samples from Amazonian floodplains was explained in 53.3 % and 22.6 %, respectively, by the edaphic factors analyzed. Taken together, the results of this study open possibilities for interpretations about the production and consumption of CH4 in wetland areas of Amazonia based on the particular characteristics of the black, white and clear floodplains, dissociating them among themselves based on active methanogenic and methanotrophic microbial communities and edaphic factors, and not just by water type.
Influence of dry and flooding on methanogenic and methanotrophic microbial communities in Amazonian black, white and clear floodplains
Keywords: Metano; Gene 16S rRNA; Comunidade microbiana ativa; Áreas inundáveis; Águas amazônicas; Methane; 16S rRNA gene; Active microbial community; Wetland areas; Amazonian water types; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA